Aggregation-induced emission with enhanced two-photon absorption of dicyanomethylene-benzopyran with polyether chain for blood-brain barrier penetration. (January 2020) - Liu, Jiejie; Liu, Dandan; Shen, Yu; Zhang, Mingzhu; Liu, Tianyan; Cao, Hongzhi; Chen, Lei; Li, Dandan; Tian, Yupeng; Tian, Xiaohe
Abstract: The potential application of high-efficiency luminescent materials with aggregation-induced emission (AIE) behaviour for central nervous system functional imaging is a promising emerging field of research. Whereas, their brain penetration and actual blood-brain barrier crossing mechanism remained scarcely understood. Herein, we report three D-π-A chromophores(DCO1-3) with AIE characteristics and two-photon activities. In particular, one of the compoundsDCO3 displays large two-photon absorption cross-sections of up to 880 GM with 90% water fraction ( f w ). Meanwhile, introduced polyether chains endow them with appropriate biocompatibility and potential for central nervous system targeting. Its blood-brain barrier (BBB) penetration capability was evaluated in the cell model, indicating promising transcytosis efficiency via microtubule trafficking. The results offer a comprehensive understanding of designing AIE fluorescent probes for further central nervous system transportation and imaging purpose. Highlights: A family of AIE fluorophoreswith satisfactory two-photon absorption property is synthesized and characterized. DCO3 demonstrates active endocytosis entry in live cells without altering cell viability. DCO3 penetrating the blood-brain barrier indicates promising transcytosis efficiency.